Chicken embryo related (CER) cell line for quantification of rabies neutralizing antibody by fluorescent focus inhibition test - Cardoso, T. C.; da Silva, LHQ; da Silva, SEL; Albas, A.; Pardo, P. E.; Tanaka, A. H.; Cossy, L. B.; Perri, SHV (Elsevier B.V., 2006)
Levels of rabies virus neutralization antibody in sera from vaccinated dogs and cattle were either measured by mouse neutralization test (MNT) or by rapid fluorescent focus inhibition test (RFFIT), performed on CER monolayers. The two tests were compared for their ability to detect the 0.5 International Units/ml (I.U.) recommended by the World Health Organization (WHO) as the minimum response for proof of rabies immunization. A significant correlation was found between the two tests (n = 211; r = 0.9949 in dogs and 0.9307 in cows, p < 0.001), good sensitivity (87.5%), specificity (94.7%) and agreement (96.6%) as well. RFFIT method standardized on CER cell system for neutralizing antibodies detection turns the diagnosis easier and less expensive, specially when a great number of samples must be tested from endemic areas as commonly found in Brazil. (c) 2005 the International Association for Biologicals. Published by Elsevier Ltd. All rights reserved.
Keywords: rabies; CER (chicken embryo related) cells; BHK-21 cells; rapid focus fluorescent inhibition test (RFFIT)